Radiation followed by OX40 stimulation drives local and abscopal antitumor effects in an anti-PD1-resistant lung tumor model - Niknam, Sharareh (Clin Cancer Res, 2018)
PURPOSE: Radiation is used extensively to treat localized cancer, but improved understanding of its effects on the immune system have increased interest in its potential systemic (abscopal) effects, particularly in combination with checkpoint inhibitors such as anti-PD1. The majority of patients either do not respond or develop resistance to monotherapy over time. Here, we investigated the efficacy of OX40 (CD134) stimulation as an alternative immunotherapeutic approach in combination with radiotherapy (XRT) in a murine model of anti-PD1-resistant lung tumors. EXPERIMENTAL DESIGN: We established a bilateral tumor model in 129Sv/Ev mice using an anti-PD1 resistant lung tumor cell line. Primary tumors were treated with intratumoral injection of an OX40 agonist antibody, given as adjuvant therapy after XRT (36 Gy in three 12-Gy fractions), while secondary tumors were left untreated to investigate abscopal outcomes. RESULTS: The combination of XRT followed by OX40 stimulation effectively inhibited local and systemic antitumor growth, limited lung metastases, and improved survival rates. This treatment regimen augmented CD4(+) and CD8(+) T cell expansion. XRT induced the expression of OX40 on T cells in tumors and spleens and increased the percentages of splenic CD103(+) dendritic cells. CONCLUSION: Our data extends the benefits of radiation to systemic disease control, especially when combined with anti-OX40 agonist to promote immunologically mediated abscopal effects. Moreover, this study provides a rational treatment approach and sequence to overcome anti-PD1 resistant poorly immunogenic tumors.